Gender Differences in The Factors associated with Hypertension in Non-Diabetic Saudi Adults—A Cross-Sectional Study - Rajaa Al-Raddadi (MDPI AG, 2021)
The association between lifestyle practices, obesity and increased BP are under-investigated. We aimed to investigate this association to identify the factors associated with hypertension and prehypertension in Saudis. Non-diabetic adults were recruited from public healthcare centers using a cross-sectional design. Recruits were interviewed using a predesigned questionnaire. Weight, height, waist circumference (WC), hip circumference (HC), neck circumference (NC) and BP were measured. The variables were analyzed by comparing the prehypertensive and hypertensive groups with the normotensive group. A total of 1334 adults were included. The study found that 47.2% of men and 24.7% of women were prehypertensive, and 15.1% of men and 14.4% of women were hypertensive. High BMI, WC, NC, and WC: HC ratios were associated with an increased risk of prehypertension and hypertension in men and women. Low physical activity was associated with an increased risk of elevated BP in men, while sleep duration of ≤6 h and sitting for ≥4 h were associated with increased risk in women. Women from central Asia, southeast Asia, and those of mixed origin had a higher prevalence of hypertension compared to those from Arabian tribes. In conclusion, prehypertension and hypertension increase with age and obesity. Gender differences were apparent in the association between several lifestyle practices and prehypertension or hypertension among various ethnic/racial groups.